Memahami Weltanschauung Al-Qurâan : Perspektif Pendekatan Kontemporer - Yusuf, Muhammad (Sekolah Tinggi Filsafat Islam Sadra, 2015)
AbstractThe classical reading methods which are literal textual as an intellectual response from Muslims scholars to social-cultural dynamic which related to their life at that time. The urgency to understand the Qurâan in a holistic manner was needed in addressing the problems of life, in addition to the development of the qurâanic study necessitates the alignment between scientific research, interpretation of the Qurâan, universal benefit and the value of wisdom in the same breath with weltanschauung of al-Qurâan. Implementation of such commentary tradition in the context of local wisdom is not intended to limit the meaning of the Qurâan text, but rather on the dialectic between interpretation, cultural and readers that can not be separated. This article tries to convey Bugis-Makassar cultural values as an example of how to implement the relevant moral ideas in accordance with the teachings of the Qurâan.Keywords: weltanschauung, the Qurâan, socio-cultural, values, beneficiariesÂ Abstrak: Metode pembacaan klasik yang bersifat literal-tekstual merupakan respon intelektual ulama terhadap dinamika sosio-kultural yang melingkupi mufasir dan masyarakatnya ketika itu. Urgensi memahami al-Qurâan secara holistik pun diperlukan dalam menyikapi persoalan hidup, di samping pengembangan studi al-Qurâan yang relevan meniscayakan adanya keselarasan antara riset ilmiah, penafsiran al-Qurâan, kemaslahatan universal serta nilai kearifan yang senafas dengan weltanschauung al-Qurâan. Implementasi dalam konteks kearifan lokal bukan dimaksudkan untuk membatasi makna teks al-Qurâan melainkan lebih pada dialektika antara penafsiran, budaya dan pembaca yang tak terpisahkan. Artikel ini mengangkat nilai budaya Bugis-Makassar sebagai contoh bagaimana menerapkan ide moral yang relevan dengan ajaran al-Qurâan. Kata-kata Kunci: weltanschauung, al-Qurâan, sosiokultural, nilai, kemaslahatan